2015
DOI: 10.2340/00015555-1901
|View full text |Cite
|
Sign up to set email alerts
|

Hand Eczema and Use of Snus (Moist Snuff) – a Population-based Study

Abstract: A possible association between use of snus (Swedish moist snuff) and hand eczema was studied. 27,466 individuals responded to questions regarding hand eczema, tobacco use and other life style factors in a Swedish Public Health Survey in 2006, response rate 58%. Of these persons, 12.2% reported daily snus use (men 22.0%, women 4.3%), 15.5% daily smoking (men 14.4%, women 16.5%). Of snus users 7.5 % reported hand eczema (men 6.5%, women 11.8%), of smokers 11.7% (men 8.6%, women 13.6%) and of non-tobacco-users 9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 22 publications
0
20
0
1
Order By: Relevance
“…1.1-11.8). The overall pooled 1-year prevalence was 9.1% (95% CI: 8.4-9.8) based on data from 301 293 individuals in 24 studies 10,12,13,17,18,21,22,[29][30][31][32][33][34][35][36][37][38][39][40][41][42] (Figure 3), the clinically determined point prevalence was 4.0% (95% CI: 2.6-5.7), based on data from 33 070 individuals in 12 studies 22,24,[43][44][45][46][47][48][49][50][51][52] (Figure S1), and the self-reported point prevalence was 3.5% (95% CI: 2.8-4.3) based on data from 211 923 individuals in nine studies (Figure S2). 8,13,17,22,23,40,[52][53][54] Comparing adults and children, there was a tendency towards higher pooled prevalence estimates for adults, although this difference was only significant for the 1-year prevalence (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…1.1-11.8). The overall pooled 1-year prevalence was 9.1% (95% CI: 8.4-9.8) based on data from 301 293 individuals in 24 studies 10,12,13,17,18,21,22,[29][30][31][32][33][34][35][36][37][38][39][40][41][42] (Figure 3), the clinically determined point prevalence was 4.0% (95% CI: 2.6-5.7), based on data from 33 070 individuals in 12 studies 22,24,[43][44][45][46][47][48][49][50][51][52] (Figure S1), and the self-reported point prevalence was 3.5% (95% CI: 2.8-4.3) based on data from 211 923 individuals in nine studies (Figure S2). 8,13,17,22,23,40,[52][53][54] Comparing adults and children, there was a tendency towards higher pooled prevalence estimates for adults, although this difference was only significant for the 1-year prevalence (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 55 studies (n = 40-65 261), 1,5,[31][32][33][34][35][36][37][38][39][40]23,[41][42][43][44][45][46][47][48][49][50]24,[51][52][53][54][55][56][57][58][59][60]25,[61][62][63][64][65][66][67][68][69][70]26,[71][72][73][74][75][27][28]…”
Section: Study Characteristicsunclassified
“…Study design included cohort (prospective (n = 13) 23,24,69,74,75,29,[36][37][38]51,52,56,58 and retrospective (n = 6) 27,44,55,57,61,62 ), case-control (n = 7), 1,25,39,46,53,64,71 and cross-sectional studies (n = 29). 5,26,[41][42][43]45,[47][48][49][50]54,59,28,60,63,[65][66][67][68]70,72,73,[30][31][32][33]…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…suggested that physical exercise was associated with a lower prevalence of hand eczema. [ 11 ] A Sweden study similarly reported that the prevalence of hand eczema was lower in individuals with high levels of physical exercise. [ 10 ] The physical exercise has been postulated to promote muscle fibers’ production of interleukin-6 (IL-6), which stimulates the production of anti-inflammatory cytokines, such as IL-1 receptor antagonist and IL-10, and inhibits the production of pro-inflammatory cytokines like tumor necrosis factor-α (TNF-α).…”
Section: Discussionmentioning
confidence: 99%